Acute Management of Maxillofacial Trauma: A Review of Literature - Bijayalaxmi Panigrahi1 , Santosh Kumar Subudhi2 , Sthitaprajna Lenka2Shibasis Biswas1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Management of trauma has progressed dramatically over the past few decades thereby reducing mortalityin the golden hour. Challenges exist, however, one such region is maxillofacial injury in a patient withpolytrauma. Because of the regions close to the brain, cervical spine and airway, serious injuries to themaxillofacial area may complicate the early treatment of a trauma patient. In case of maxillofacial injuries, thenormal procedures of airway respiration and circulation (ABC) management are also changed or augmentedby other approaches. In an often-challenging situation these modifications have their own difficulties andpitfalls.